Uji Beberapa Zat Pengatur Tumbuh Terhadap Pertumbuhan Setek Lada Perdu (Piper nigrum L.) - Wahyudi Wahyudi; Made Deviani Duaja; Elis Kartika (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Pepper (Piper nigrum L.) is a commodity of high economic value, but the production is still low. The main reason is the lack of availability for good pepper seedling. Pepper has been commercially propagated by cuttings. To optimize pepper cutting growth could be done through the application of plant growth regulator (PGR). PGR can also be obtained from plant extracts. Some parts of the plant can be used as an exogenous growth regulator hence it contains many hormones that plants need. This experiment was conducted at Teaching and Research Farm, Universitas Jambi to select the best plant extract as an exogenous growth regulator that could induce root and growth of pepper cutting. Five plant extracts, animal urine, and synthetic growth regulator were used as treatment namely: Rootone-F as control, coconut water (Cocos nucifera L.), cow urine, extract of mung bean sprouts (Vigna radiata) + moringa leaf extract (Moringa sp.), young corn (Zea mays) seed extract + moringa leaf extract, young corn seed extract + moringa leaf extract, bamboo shoot extract + banana hump (Musa paradisiaca) extract. The experiment was set in the form of randomized complete design with three replications. Result revealed that synthetic plant growth regulators and plant extracts as exogenous growth regulator have a significant effect on the growth of pepper cuttings. Coconut water gave the best of pepper seedling growth based on the percentage of live seedling, percentage of cutting sprouts, shoot length, root length and shoot dry weight.